A Mediterranean Dietary Intervention in Female Carriers of BRCA Mutations: Results from an Italian Prospective Randomized Controlled Trial - Eleonora Bruno (Cancers, 2020)
Background: Women carriers of BRCA1/2 mutations face a high lifetime risk (penetrance) of developing breast and/or ovarian cancer. Insulin-like growth factor I (IGF-I), body weight and markers of insulin resistance affect BRCA penetrance. We conducted a multicenter prospective two-armed (1:1) randomized controlled trial (NCT03066856) to investigate whether a Mediterranean dietary intervention with moderate protein restriction reduces IGF-I and other metabolic modulators of BRCA penetrance. Methods: BRCA carriers, with or without a previous cancer, aged 18–70 years and without metastases were randomly assigned to an active dietary intervention group (IG) or to a control group (CG). The primary endpoint of the intervention was the IGF-I reduction. Results: 416 women (216 in the IG and 200 in the CG) concluded the six-month dietary intervention. The IG showed significantly lowered serum levels of IGF-I (−11.3 ng/mL versus −1.3 ng/mL, p = 0.02), weight (−1.5 Kg versus −0.5 Kg, p < 0.001), waist circumference (−2 cm versus −0.7 cm, p = 0.01), hip circumference (−1.6 cm versus −0.5 cm, p = 0.01), total cholesterol (−10.2 mg/dL versus −3.6 mg/dL, p = 0.04) and triglycerides (−8.7 mg/dL versus + 5.5 mg/dL, p = 0.01) with respect to the CG. Conclusions: A Mediterranean dietary intervention with moderate protein restriction is effective in reducing IGF-I and other potential modulators of BRCA penetrance.